Three dimensional CT analysis of the change in rotational alignment in double level osteotomy after double level osteotomy performed for varus osteoarthritic knees - Shunichiro Kambara; Hiroshi Nakayama; Ryo Kanto; Shintaro Oonishi; Makoto Kanto; Shinichi Yoshiya; Toshiya Tachibana; Tomoya Iseki (Elsevier, 2021)
Purpose: To analyze the change in rotational alignment caused by double level osteotomy (DLO) based on comparative three-dimensional image analysis of pre- and postoperative CT images. Methods: Pre- and postoperative CT examination of the lower extremities were performed with informed consent for 39 consecutive knees undergoing DLO for varus knee deformity. The DLO procedure consisted of closed wedge distal femoral osteotomy (CWDFO) and open wedge high tibial osteotomy (OWHTO). Among those cases, 20 knees complicated with hinge fracture at the osteotomy site were excluded from the analysis to eliminate a confounding factor affecting the results. Consequently, data obtained from 19 knees were subjected to the study analysis while osteotomies with hinge fractures complications were excluded from the study. In the three-dimensional CT image analysis of axial plane images, femoral torsion (the angle between midline along the femoral neck axis and the tangent of the posterior edges of the medial/lateral femoral condyles) and tibial torsion (the angle between the tangent of the posterior edges of the medial/lateral tibial condyles and the transmalleolar axis) were measured. The torsion angle was measured in each of the femurs and the tibias on both pre- and postoperative CT axial images, and the change induced by the osteotomy was calculated and statistically(using Wilcoxon signed-rank test) compared. Results: The mean pre- and postoperative femoral torsion (anteversion) angles were 29.3° and 31.4° with a significant postoperative increase in internal rotation of the bony segment distal to the osteotomy(P = 0.002). On the tibial side, the mean pre- and postoperative torsion angles were 26.5° and 25.7°, indicating no significant postoperative change(P = 0.199)（NS）. Conclusions: This study showed that the DLO procedure (combining CWDFO and OWHTO) increased torsion (anteversion) of the femur by 2.1° on average while inducing no significant rotational change on the tibial side.